Promosi Dan Harga Terhadap Keputusan Pembelian Sepeda Motor Yamaha R15 pada PT. Hasjrat Abadi - Ume, Andika Candra; Areros, William A.; Tatimu, Ventje (Productivity, 2020)
This study aims to determine the effect of promotion and price on purchasing decisions for Yamaha R15 motorcycles at PT. Hasjrat Abadi Manado. This type of research is quantitative research. In this study sampling using a Likert scale. The research data were obtained by distributing questionnaires about promotions, prices, and purchasing decisions to 71 respondents who owned a Yamaha R15 motorcycle at PT. Hasjrat Abadi Manado. Data analysis techniques in this study used SPSS version 25 for the window. The results of this study indicate that promotion has a positive effect on purchasing decisions for Yamaha R15 motorcycles, and price also has a positive effect on purchasing decisions. Promotion and price simultaneously influence the purchase decision. The relationship level of the two promotion variables and price to the purchase decision has a positive relationship.